Wyposażenie powiatów ziemskich woj. dolnośląskiego w urządzenia infrastruktury technicznej służące ochronie środowiska i możliwości zmian w tym względzie po przystąpieniu Polski do UE - Szymańska, Joanna (Providing Technical Equipment for Land Administrative Districts in Lower Silesia Voivodship Which Are Used to Protect Environment and Possibilities of Changes after Joining the EU, 2005)
The paper presents ecological problems of rural areas in Lower Silesia Voivodship. The author shows that disproportion exists in providing villages with sewer system and water-supply service. The author sets off possibilities of improving this situation after joining the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 343-347